Uncovering the Full Potential Utilization of Petroleum Reserves Residue for Sustainable Energy Supply - Khan, Muhammad Asif; Hakeem, Luqman; Ali, Muhammad Junaid; Hussain, Muhammad Shakir (ASEAN Journal for Science and Engineering in Materials, 2025)
In the framework of international efforts to achieve carbon neutrality, this research investigates the potential of petroleum reserve residue as a sustainable energy source, focusing on unconventional crude oils. The discovery of alternative resources, such as bitumen, heavy crudes, and high-acid crudes—which combined make up almost two-thirds of the world's oil reserves—has become necessary due to the depletion of traditional oil stocks. This study looks at the difficulties in processing these non-conventional oils, especially their high acidity, which poses environmental risks and severely corrodes refinery equipment. The article discusses a revolutionary method for upgrading and treating these unconventional crudes without the need for external catalysts or molecular hydrogen, utilizing supercritical fluids (supercritical methanol and water). The evaluation emphasizes how well this process works to produce synthetic crude oil that is appropriate for use in refineries that are currently in operation by lowering asphaltenes, contaminants, and total acid numbers (TAN). There are suggestions for more study into low-temperature, low-pressure catalytic alternatives, although the economic feasibility of high-temperature, high-pressure processes is questioned. One important step in striking a balance between technical growth and environmental preservation is the emphasis on the potential of this methodology in promoting sustainable energy production and lowering environmental pollution.